Re-roteamento rápido em redes MPLS (multiprotocol label switching): um método de proteção de múltiplos segmentos - Fonseca, Marcos Guimarães (2005)
The research of fault recovery techniques in computer networks plays an important role for many applications, specially for the real-time ones. The combined use of Multiprotocol Label Switching (MPLS) and Traffic Engineering (TE) provides faster and more efficient fault recovering techniques than those obtained through other protocols and techniques. As a consequence, packet delays and losses are significantly reduced. Three methods based on MPLS technology are discussed in this master thesis: The Global Path Protection Method (GPPM), the Reverse Path Protection Method (RPPM), and the Multiple Segments Protection Method (MSPM). These methods were implemented by using the Network Simulator (NS2). From simulation results, one can see that MSMP is more efficient than GPPM in terms of packet loss and more efficient than RPPM in terms of packet delay.